Macierzyństwo jako klucz do refleksji na temat godności i powołania kobiety w myśli Jana Pawła II - Pryba, Andrzej (Poznańskie Studia Teologiczne, 2022)
The work presents the basics of St. John Paul II’s reflection on women, their dignity, nature and vocation, pointing to motherhood as the key to the development of the Pope’s teaching, organizing his statements. An analysis of the writings of John Paul II shows that, regardless of his reflections on human dignity, he supports his reflections on women by emphasizing their ability to physical motherhood, assuming the impact of this ability and the possibility of its realization on the tasks and obligations of women towards all humanity. An analysis of the Pope’s writings shows that he did not devote the same amount of attention and space to reflection on the meaning of masculinity and the vocation of men.